Implementation of Supervision and Evaluation of Multicultural Education in Effective Islamic Religious Learning Models at SMPIT As-Sunnah Makassar - Arifuddin Arifuddin; Ahmad Yani; Ismail Ismail (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This study aims to examine the implementation of supervision and multicultural education evaluation within an effective Islamic Religious Education (IRE) learning model at SMP Islam Terpadu (Integrated Islamic Junior High School) As-Sunnah Makassar. Multicultural education plays a vital role in shaping students’ tolerant and inclusive character, especially within a school environment grounded in Islamic values. A descriptive qualitative approach was employed using a case study method. Data collection techniques included classroom observation, in-depth interviews, and documentation. The findings reveal that supervision is carried out in an educative and developmental manner, encouraging teachers to design contextual, collaborative, and integrative learning strategies that align with multicultural values. The dominant instructional model applied is Contextual Teaching and Learning (CTL), which is further supported by cooperative learning and problem-based learning approaches. Evaluation is conducted comprehensively and continuously, covering cognitive, affective, and psychomotor domains, while also incorporating reflection and character development processes. Teachers act not only as instructors but also as role models who embody Islamic values in their daily interactions with students. This study underscores the importance of synergy between educative supervision, relevant learning models, and continuous evaluation in fostering effective and contextual IRE learning within a multicultural educational setting.